January Effect on Stock Returns: Evidence from emerging Balkan equity markets - Milošević Avdalović, Snežana; Milenković, Ivan (Industrija, 2017)
The motivation for testing anomalies in the selected financial markets in the region was primarily to help investors to devise a viable investment strategy. Taking into account the difficult circumstances faced by the capital markets in developing countries, their efficient operation is under question. While the calendar anomalies in the developed capital markets have been studied intensively, emerging stock markets have received less attention. The aim of this paper is to test historical data on movements of stock exchange indexes in the region, and in that way the possibility of gaining beyond average yields on capital in certain calendar months during the year, also known as the January effect. The paper aims to test the efficient market hypothesis (in terms of the presence or not of the ‘January effect’) in the financial markets in the region by using daily data of regional stock market indexes. Panel data analysis includes daily data during the period from 2008 to 2014 for the stock exchanges in the emergent economies of Serbia, Bosnia and Herzegovina, Macedonia, Montenegro, Croatia, Romania and Bulgaria. However, in this study it has been proven that the traditional January effect is present only on the stock market in Macedonia. The obtained results on capital markets in selected countries in the region indicate weak sustainability of the efficient market hypothesis in most of the observed countries in the region and the presence of calendar anomalies.